Determinant Factors Influencing Purchase Intention of Electric Cars (BEV) in Indonesia - Putri, Alfdian Wizqi; Aruan, Daniel Tumpal Hamonangan (Syntax Corporation, 2025)
In response to the escalating global carbon emissions, electric vehicles have emerged as a viable technology capable of mitigating the rise in carbon emissions by offering a more eco-friendly energy source in the transportation sector. This research aims to analyze the impact of perceived usefulness, perceived ease of use, attitude, subjective norms, perceived behavioral control, subjective norms, price value, perceived risk, environmental self-image, infrastructure barrier, monetary and non-monetary incentive policy, and knowledge toward purchase intention in Indonesia using the extended of the combined theory of planned behaviour and technology acceptance model (C-TAM-TPB). employ a quantitative survey with 406 Indonesian adults (over 17, with driver's licenses, no prior EV ownership) recruited through social media (Instagram, Facebook, WhatsApp) between October 17 and November 10, 2023. This research uses quantitative approach 406 Indonesian citizens who lives in Indonesia, have a driving license, and have not had electric car. Distributed The model was evaluated by employing structured questionnaires obtained from 406 respondents in Indonesia and analyzed using PLS-SEM. The findings indicate that perceived behavioral control, price value, non-monetary incentive policy, and knowledge have positive effects and significant toward intention to purchase electric cars (BEV). Both infrastructure barriers and perceived risk have a negative effect on intention. This research also find knowledge considered as significant factor to influence the attitude, perceived usefulness, price value, dan purchase intention.